Student Planning and Educational Interaction at SMP Plus Al-Istiqomah - Khaerunnisa, Asri (UIN Sunan Gunung Djati Bandung, 2024)
Educational interaction is an interaction that occurs in the teaching and learning process and certainly involves two parties, namely educators (teachers) and students (students). This educational interaction certainly does not just happen, but there are provisions that must be carried out so that it can be implemented properly and achieve the goals of education itself. Although every school institution, especially teachers, and every student has different problems in this educational interaction process, these issues must be overcome so that learning can be conveyed properly by the teacher to his students. This research is qualitative research, which is a method that focuses on reasoning based on social reality objectively. Thus, this study seeks to collect objective data or information in the field regarding student planning and educational interaction at Al-Istiqomah Junior High School. Therefore, this research aims to describe the process of student planning and educational interaction at SMP Plus AL-Istiqomah Garut school